Assessment of Anchorage Methods and FRP Laminate Strengthening Configurations for URM Walls Under In-Plane Loading (2018)
In order to ensure a continuous and reliable path for the lateral loads caused by earthquake or wind forces, FRP-strengthened masonry walls that are part of the lateral load resisting system of a building require the joint work of the FRP strengthening to resist tensile stresses in the masonry and anchorage to the boundary structural elements (foundations or beams) to transfer the loads. This article presents the results of an investigation on the assessment of anchorage methods and FRP strengthening configurations for unreinforced masonry (URM) walls subjected to in-plane loads. Fourteen masonry walls were constructed for this experimental program. All of the walls were built with hollow clay bricks, typical of URM structures in Colombia and other parts of the world. The specimens for this investigation included slender and squat walls. The dimensions of the slender walls were 1.20 m. [4 ft] long, 1.90 m. [6.2 ft.] high, and 120 mm [4.8 in.] thick. The dimensions of the squat walls: 2.50 m. [8.2 ft.] long, 1.90 m. [6.2 ft.] high, and 120 mm [4.8 in.] thick. The walls were strengthened using two configurations: (1) Layout ‘H’ involving horizontal CFRP laminates along on wall side, and vertical CFRP laminates at each wall toe on one side of the wall, and (20 Layout ‘X’ involving diagonal CFRP laminates oriented at approximately 45 degrees on one side of the wall. Four anchor systems were evaluated: (1) System 1 (CFRP anchors embedded in the base beam), (2) System 2 (CFRP bonded to the base beam), (3) System 3 (FRP bonded to grout blocks), and (4) System 4 (FRP wrapped around grout blocks). The walls were tested in two series: (1) Series 1 – Monotonic Loading, and (2) Series 2 – Cyclic Loading. The test results demonstrated that Anchor System 4 was the most effective anchorage system. The walls strengthened with Anchor System 4 failed due to rupture of the CFRP laminates wrapped around the grout block. In general, the largest increases in in-plane capacity, when compared to the control walls, were observed in the slender walls. The walls with the ‘H’ Layout showed more ductility and less degradation of the lateral stiffness than the walls strengthened with the ‘X’ Layout.